The use of high-strength cast iron with a ferritic structure for the reciprocating displacement system of the internal combustion engine pistons and the improvement of its operation parameters - S. N. Yankevich; I. N. Khrol; M. S. Koval’ko; I. I. Palidavets (Литьë и металлургия)
A study of compositions of samples of high‑strength cast iron, the use of which is possible in the development of an internal combustion engine with an improved design of a combined reciprocating conversion system, has been carried out. A number of research methods were carried out, including isothermal hardening. The optimal combination of strength and plastic properties have samples from high‑strength cast iron containing, wt.%: 2.9–3.1 C; 3.2–3.5 Si; 0.28–0.31 Mn; 0.7 Cu; 0.35 % Mo and 0.025B. Also, in the course of the study, the possibility was considered and studies were conducted on quenching cast iron in a spray chamber and jet cooling, as an alternative to traditional quenching in molten salts. The data obtained indicate that during jet‑air isothermal quenching, the structure of cast iron is completely and uniformly formed along the cross‑section, while providing a level of tensile strength up to 950 MPa, hardness up to 360–370 NV while maintaining elongation at tension up to 8 %. The use of such a class of cast iron in improved KSPVPP will both increase the life of the internal combustion engine as a whole, and improve its operational characteristics – reduce noise and reduce the weight of the structure.